2015
DOI: 10.1371/journal.pone.0130552
|View full text |Cite
|
Sign up to set email alerts
|

Viruses Occur Incorporated in Biogenic High-Mg Calcite from Hypersaline Microbial Mats

Abstract: Using three different microscopy techniques (epifluorescence, electronic and atomic force microscopy), we showed that high-Mg calcite grains in calcifying microbial mats from the hypersaline lake “La Salada de Chiprana”, Spain, contain viruses with a diameter of 50–80 nm. Energy-dispersive X-ray spectrometer analysis revealed that they contain nitrogen and phosphorus in a molar ratio of ~9, which is typical for viruses. Nucleic acid staining revealed that they contain DNA or RNA. As characteristic for hypersal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…These mineral grains incorporated in the organic matrix can be derived from the substratum, from external inputs or through the precipitation of mineral particles. The biofilms show the clear presence of fine layers of carbonate grains (Figure 5E), which turned out to be high-Mg calcite [19]. Ludwig et al [26] reported that the precipitation of these grains was driven by photosynthesis that results in higher pH values, locally, in the mat.…”
Section: Coleofasciculus Chthonoplastes Microbial Mats As Stromatolitesmentioning
confidence: 96%
See 2 more Smart Citations
“…These mineral grains incorporated in the organic matrix can be derived from the substratum, from external inputs or through the precipitation of mineral particles. The biofilms show the clear presence of fine layers of carbonate grains (Figure 5E), which turned out to be high-Mg calcite [19]. Ludwig et al [26] reported that the precipitation of these grains was driven by photosynthesis that results in higher pH values, locally, in the mat.…”
Section: Coleofasciculus Chthonoplastes Microbial Mats As Stromatolitesmentioning
confidence: 96%
“…The phylogenetic study by Bachar et al [18] has confirmed the presence of 16S rRNA gene sequences affiliated to the Chloroflexaceae family some of them very closely related to the Candidatus Chlorothrix halophila (see Figure 5C). Multiple white layers of calcium carbonate were observed in the mat (see Figure 5E), which have been identified as high-Mg calcite [19]. In addition, diatoms sometimes occurred in the mat, particularly on the top surface layer, particularly during spring.…”
Section: Lake Sciences and Climate Change 52mentioning
confidence: 97%
See 1 more Smart Citation
“…10). 5 Preliminary investigations have also demonstrated that viruses from the hypersaline lake occur and are incorporated in biogenic carbonate, suggesting that virus may be mistaken for nanobacteria and play a role in initiating mineralization (De Wit et al, 2015;Pacton et al, 2014;Perri et al, 2017). The viral drive during the biogenic carbonate precipitation in hypersaline lakes is attributed to either an indirect route, involving silicified viruses as an intermediate phase during diagenesis (Pacton et al, 2014) or a direct incorporation of amino acids polymerized with viral proteins into growing high-Mg calcite crystals (De 10 Wit et al, 2015).…”
Section: +mentioning
confidence: 99%
“…Furthermore, viral particles could act as nucleation sites for different mineral precipitation. In the past few years, researchers have investigated that the capsid of viruses can interact directly with elements in solutions and thus potentially mediate the formation and precipitation of different minerals (Daughney et al, 2004;Kyle et al, 2008;Peng et al, 2013;Pacton et al, 2014;De Wit et al, 2015;Laidler and Stedman, 2010). It has been widely 5 studied that viruses can interact with iron minerals under both marine system (including experimental conditions) (Daughney et al, 2004;Bonnain et al, 2016) and in the natural low pH acid mine drainage environment (Kyle et al, 2008;Kyle and Ferris, 2013).…”
mentioning
confidence: 99%